The evolutionary hypothesis in the functional analysis of dyslexia. Linguistic approach to the case study in twinity - Jiménez Ruiz, Juan Luis (2023)
Dyslexia is a disorder in the written use of language due to visuospatial weakness in the perception of linguistic forms. This paper postulates that a possible functional characterization of the deficits of a linguistic nature in patient speakers who present dyslexia when a full acquisition of reading and writing is not yet assumed will favor both the diagnosis and the intervention proposal. To demonstrate this hypothesis, we study the case of two twin patient-speakers who share the diagnosis of dyslexia, with the aim of checking the genetic-hereditary nature of the pathology and proposing specific therapies based on linguistic functional analysis. We thus present the theoretical framework that allows the historical knowledge and definitions offered on this disorder, the difficulties involved in its etiology, and the different models of intervention that currently exist to alleviate it. Then we then carry out a case study of the two related subjects, verifying, from the results of the study, that both siblings suffer a moderate reading delay with inversion and rotation problems, and a writing with problems also of inversion, rotation and dysgraphia. The level of dyslexia, although similar, is not identical, suggesting different intervention proposals).